Expression and clinical significance of NLRC5 in hepatocellular carcinoma - Xiangyu Ma; Shangkun Ning; Tong Sun; Mei Liu; Jibing Liu (Cancer Biology & Therapy)
NLRC5, the largest member of the nucleotide-binding and oligomerization domain (NOD)-like receptor (NLR) family, has been reported to participate in the regulation of immune function and is associated with chronic inflammatory diseases. However, the biological function of NLRC5 in hepatocellular carcinoma (HCC) has not been fully demonstrated. The aim of this study is to evaluate NLRC5 expression in the tumor tissues of HCC patients undergoing surgical treatment, assess its prognostic value, and explore its relationship with critical immune-related molecules within the tumor microenvironment. A total of 100 patients with hepatitis B virus-associated HCC receiving surgical treatment were enrolled in the study. Immunohistochemical results were obtained by scoring the intensity of cellular staining and the percentage of positive cells in the tissue sections. The association between NLRC5 expression levels and the main clinicopathological factors was analyzed by Chi-square test method. The prognostic values were analyzed by COX regression model and the Kaplan-Meier survival curve. Receiver operating characteristic (ROC) curve analysis was performed to assess the predictive performance of NLRC5 in postoperative patients with HCC. IHC showed that high expression of NLRC5 was observed in 67% of HCC tissue samples. Chi-square test showed that NLRC5 was a risk factor associated with tumor number, satellite nodule, and envelope invasion. Kaplan-Meier survival curves and COX survival analysis showed that high expression of NLRC5 was significantly associated with decreased overall survival (OS) in HCC patients (HR = 1.79, 95% CI 1.03–3.12, p = .041). However, univariate logistic regression analysis revealed that NLRC5 showed positive relationship with GZMB and CD8α suggesting its role in immune escape of HCC. ROC curve analysis showed that the combination of tumor number, envelope invasion, and NLRC5 expression (area under the curve = 0.824, sensitivity = 77.30%, specificity = 82.4%) can more accurately evaluate the prognosis of HCC patients compared to the combination of only tumor number and envelope invasion (area under the curve = 0.690, sensitivity = 43.9%, specificity = 94.1%).NLRC5 plays a crucial role in progression of HCC and can be considered as a potential prognostic and predictive biomarker. Targeting NLRC5 may provide an attractive therapeutic approach for HCC.